Pengaruh Pembelajaran Kecerdasan Majemuk Secara Daring dan Luring Terhadap Hasil Belajar Mahasiswa PGSD - Hartanto, Nizar; Nasik, Fuad Naufal; Wibowo, Ibnu Dwi; Al ‘Aufa, Muhammad Zahran; Wijayanti, Berliana Nindya (Elementary Education Journal, 2022)
Background: The problem of this research originates from the exchange of learning methods in multiple learning courses that use two learning methods, including using the offline method and the online method. This study aims to determine student learning outcomes using the online method, and learning outcomes using the offline method, is there a difference student learning outcomes using online learning methods with offline learning methods. Method: This type of research is experimental research which is quantitative research. This research was conducted at the Muhammadiyah University of Surakarta, with the research subjects being students of class D multiple intelligences at the Muhammadiyah University of Surakarta, totaling 20 students. The type of data used is primary data, namely post-test data on student learning outcomes online and offline for class D in the multiple intelligences subject at PGSD UMS Academic Year 2022/2023. The sampling technique used is Stratified Random Sampling. The data collection technique in this study was the post test. The data analysis technique used was the t test with a significance level of the analysis results determined at 0.05 (5%). Result: The results of this study explain that there are differences in learning outcomes using the online method and using the offline method seen from the average student learning outcomes, the offline learning method is higher than the online learning method based on hypothesis testing with the acceptance criteria for hypothesis testing, namely the sig value (2- tailed) online and offline learning is less than 0.05, so there is a significant difference in learning outcomes between learning using the online method and using the offline method for D class students in the Multiple Intelligences subject at PGSD UMS. Implication: The implications of this study are: First, the elementary schools' headmasters in Indonesia should enrich the teachers' knowledge and insight related to multiple intelligences. Second, the government, supported by researchers, has to design an excellent assessment system to solve time limitations. Novelty: The present study revealed the implementation of multiple intelligencesin elementary school comprehensively.